ANALISIS EFEKTIFITAS PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT DENGAN PINJAMAN MODAL USAHA (Studi Kasus Penerima Pinjaman Pada Desa Torongrejo, Kecamatan Junrejo, Kota Batu) - Putra, Saddam Krisiandry; tono, Supar (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aimed to determine the effect on the Business Capital Loan improve household incomes in the loan recipient Torongrejo as well as to determine the effectiveness of the program on poverty alleviation through income communities seen after receiving the loan with the level of poverty line. The data used are primary and secondary data obtained from the Central Statistics Agency (BPS) and the Village Office Torongrejo and Related Institutions supported  by an  interview to Business Capital  Loan recipients. Based on information from the Central Bureau of Statistics poverty in its annual Batu not show a significant reduction rate, this is an important consideration  given the level of poverty line continues to increase  each him. In this study, there are  two research  focus is the increase  in income after  receiving the loan  and  the effectiveness  of the program  on poverty alleviation. Business Capital Loan programs are proven to increase the income of the recipient community but this loan program is less effective in reducing poverty on loan offenders, the proof is carried out with Wilcoxon test and the comparison of income levels with the level of poverty line.   Keywords: Analysis, Effectiveness, Program  for  Community Empowerment, Business Capital Loan